Current Leadership Behaviours in Nepali Public Enterprises: Implications for Efficiency and Accountability - Khanal, Shrimani Raj; Soneja, Sakshi (A Bi-annual South Asian Journal of Research & Innovation, 2025)
This article explores the critical role of leadership in shaping the performance, accountability and organisational culture of public enterprises (PEs) in Nepal. These issues have led to poor service delivery, low employee motivation and diminished public trust. It highlights the dominance of bureaucratic leadership, political patronage in leadership appointments and reactive management behaviours. All contribute to operational inefficiencies and hinder organisational growth. Based on these challenges, the article proposes a set of recommendations for leadership reforms. It included the promotion of transformational leadership, merit-based appointments, leadership training and enhanced accountability mechanisms of public enterprises in Nepal.